FORMULASI NON PROSECUTION AGREEMENT (NPA) DI INDONESIA TERKAIT TINDAK PIDANA PENCUCIAN UANG DENGAN PIDANA ASAL TINDAK PIDANA KORUPSI GUNA MEWUJUDKAN NILAI KEMANFAATAN - Patmos, Yan (PT. Hafasy Dwi Nawasena, 2023)
Since the reform era until now various efforts and efforts to prevent and eradicate corruption have been made by the government, but corruption in Indonesia still exists, in the context of development in all fields of life. One of the most rampant corrupt practices in Indonesia is the practice of money laundering, which does not show clear or transparent activities as well as ordinary crime. Normative legal research is used as a research methodology. The purpose of the perpetrators disguising or bleaching the assets of the illegal business is to protect or cover up their criminal activities or illegal business which is the source of funds or money to be cleaned or laundered. Normative research focuses on a list of positive, systematic laws and concepts about the applicable law. This research uses secondary legal sources, which are evaluated through qualitative descriptive analysis. . The cost of handling a case that is not small becomes an additional problem in the settlement of money laundering cases with criminal origin. The absence of Asset Forfeiture Law is also an obstacle in terms of law enforcement. Problems arising from operational costs in pursuing TPPU assets and their maintenance are sometimes not balanced with the value of these assets through the state auction system. Therefore, legal development is needed so that the enforcement of criminal offenses by law.